Homicidio por jóvenes de Neiva; registros del delito y modalidades a partir de la implementación de la Policía Metropolitana entre los 2012-2019 - Manrique Sierra, Fabian; Coronado Pulido, Jhon (Revista revoluciones, 2023)
The objective of this research was to analyze the records of crime and sociodemographic factors that have the practice of homicide produced by young people in the city of Neiva and its modalities together with the implementation of the Metropolitan Police of Neiva. The methodology developed was of mixed cut from a descriptive and interpretative scope and under a case study design. The data collection techniques were documentary analysis and survey; the sources were selected by non-probabilistic sampling method by convenience. The findings allowed identifying that with the implementation of the Neiva metropolitan area, the homicide rates have decreased by 48% respectively, since the operational and preventive strategies have advanced in the limitation of crime in young people, however, it is found that these strategies have internal and external weaknesses in the sectorization and deepening of the structural and intermediate factors of crime at the local level and there is a lack of inter-institutional articulation with governmental entities, in addition to this, it is recognized that according to the sociodemographic characteristics of the offender is a population immersed in social, economic and family risk factors that alienate and generate this crime.